Enhancing Corporate Environmental Performance Through Green Human Resource Management - Rizqulloh, Ahmad Dafa Bahits; Mutmainah, Rouf Esa; Lataruva, Eisha (LifeSciFi, 2024)
Green human resource management is becoming a major focus in organizations that play a role in environmental performance. With increasing awareness of the positive impact of business activities on the environment, companies are faced with the challenge of adopting Green Human Resource Management (GHRM) practices. The concept of Green Human Resource Management (GHRM) involves the integration of environmental considerations into Human Resource (HR) policies, with the aim of encouraging sustainable resource utilization and increasing ecological awareness within the organization. It aims to engage employees in practices that support the environment, raise awareness of environmental issues, and strengthen a culture of sustainability. The research method used in this study is a literature review on Green Human Resource Management, which includes various types of literature on the topic. This study aims to evaluate the impact of green human resource management on improving corporate environmental performance. The results show that the green training, and Involvement consistently have a positive impact on Corporate Environmental Performance (CEP).